2011
DOI: 10.5143/jesk.2011.30.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Work-related Musculoskeletal Disorders among Agricultural Workers

Abstract: Objective: The aim of this paper is to survey the gender differences Work-related musculoskeletal disorders among agriculture workers. Background: The number of occupational injuries has been decreasing trend in Korea, but it has been increasing in agriculture. The ratio of women worker shows steady increasing trend among the agricultural worker in Korea. Method: This study investigated through the questionnaire to 358 agricultural workers who are working for agriculture located in Gyeongnam, Gyeongbuk and Jej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
6
1
Order By: Relevance
“…In the present study, female farmers showed higher risk than males for hand pain. This may be because female Korean farmers often perform tasks that require repetitive use of the hands and fingers [27, 28]. Moreover, females in the present study showed significantly higher time spent on housework than males and, as a result, the working time, including housework, may be higher in female farmers than in male farmers.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In the present study, female farmers showed higher risk than males for hand pain. This may be because female Korean farmers often perform tasks that require repetitive use of the hands and fingers [27, 28]. Moreover, females in the present study showed significantly higher time spent on housework than males and, as a result, the working time, including housework, may be higher in female farmers than in male farmers.…”
Section: Discussionmentioning
confidence: 65%
“…In a study that investigated the difference in musculoskeletal disorders according to gender among 358 Korean farmers, the average daily working time for female farmers (9.6 h) was longer than that of male farmers (9.2 h). Since the female farmers also tended to be solely responsible for housework, they had a greater burden [27, 28]. It is postulated that female farmers showed a higher risk of hand pain than males because housework mostly involves the use of the hands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with a previous study, which reported that men are 3.5 times more likely to incur an occupational injury [ 37 ]. Further, a study on production operators, agricultural workers, and workers involved in repetitive tasks reported that the prevalence of musculoskeletal pain was higher among women than among men [ 38 39 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also gender differences in agricultural work-related injuries, where female farmers experience more injuries due to "falls" and "excessive force/movement", while male farmers report more injuries due to "agricultural machinery", "collision with objects", "entanglement/pinching", and "animal injuries" [11]. [12] also reported that female farmers experience more work-related musculoskeletal disorders than male farmers. The Rural Development Administration [11] reports that male farmers are more exposed to noise, exhaust gas, and handling of heavy objects, while female farmers experience more musculoskeletal symptoms and visual impairment than male farmers.…”
Section: Introductionmentioning
confidence: 99%